Prevalence of Anterior Ethmoidal Canal Dehiscence in Anterior Skull Base in Patients Undergoing Endoscopic Sinus Surgery: A Multicentered Study - Goran Latif Omer; Lavan Hussein Abdulrahman; Gashbin Edris Yahya; Gardun Ghafur Mhammad Amin (Journal of Head & Neck Physicians and Surgeons)
Context: Although the anterior ethmoidal artery (AEA) is an important landmark in skull base surgery, due to its highly variable position in accordance with the ethmoidal roof, it is very vulnerable to injury during endoscopic sinus surgery (ESS). Aim: Due to the lack of studies emphasizing the necessary anatomical specifications and anomalies that need to be recognized before major surgeries such as ESS, this study aims to reveal anatomical variations of AEA with the hopes of aiding surgeons avoid these complications. Subjects and Methods: This study is a cross-sectional observational multicentered study conducted through a retrospective review of consecutive computed tomography scans of the peripheral nervous system spanning from April 2022 to April 2024. It includes 118 patients with or without AEA canal dehiscence, either partial or complete dehiscence. Results: The average age of the patients was 40.7 years. Among the total 118 patients, 88 (74.6%) patients did not have AEA canal (AEAC) dehiscence but among the 28 cases that did, bilateral AEA canal dehiscence was the most common. Furthermore, a direct correlation was found between many variables such as right and left AEA length, each with their canal dehiscence and each with their relation to the skull base. Conclusions: We conclude that preoperative assessment of the AEA course is crucial to ensuring the safety and effectiveness of paranasal sinus surgery. This is because great variations exist among individuals with regard to their AEAC status.